ANALISIS HUBUNGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITYDENGAN KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arvey Fahliyfi (Media Riset Akuntansi, Auditing & Informasi, 2014)
The purpose of this research is determine the quality of Corporate Social Responsibility disclosure on the Mining Company’s through annual report, and  analyze the relationship between social disclosure and financial performance on Mining Companies that are listed on Indonesia Stock Exchange. The sample in this research consist of 11 companies listed in Indonesia Stock Exchange in 2006, 2007, and 2008 period. Purposively used in this research. This research measures the variable of Corporate Social Responsibility by using a list of 79 items checklist issued by the Global Reporting Initiative (GRI) Guidelines, which is divided into 6 categories, there were Economy, Environtment, Human rights, Employee behavior, Responsibility of the product and Community. The result of this research indicates that Corporate Social Responsibility have positive relation with ROA and ROE company. This condition indicates company that have good finance performance, then disclosure of corporate social responsibilty will be wide, and company that wide disclosure of corporate social responsibility then company's finance performance will be good.